2012
DOI: 10.1212/wnl.0b013e318264e36b
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelets vs anticoagulation for dissection

Abstract: www.dissection.co.uk, ISRNCTN44555237.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 12 publications
2
110
1
Order By: Relevance
“…12 A recent meta-analysis combining data from the nonrandomized arm of CADISS with results from previous nonrandomized studies failed to provide clear guidance on the relative efficacy of anticoagulation compared with antiplatelet therapy in the prevention of stroke after acute extracranial carotid and vertebral artery dissection. 13 Because intracranial extension of the carotid artery dissection (as seen in our patient) increases the risk of subarachnoid hemorrhage, antiplatelet therapy tends to be preferred over anticoagulation. 3,4 Still, analysis of data from a large singlecentre registry indicated that patients with intracranial artery dissection without subarachnoid hemorrhage had a favourable outcome with anticoagulants.…”
Section: Management Of Carotid Dissectionmentioning
confidence: 85%
“…12 A recent meta-analysis combining data from the nonrandomized arm of CADISS with results from previous nonrandomized studies failed to provide clear guidance on the relative efficacy of anticoagulation compared with antiplatelet therapy in the prevention of stroke after acute extracranial carotid and vertebral artery dissection. 13 Because intracranial extension of the carotid artery dissection (as seen in our patient) increases the risk of subarachnoid hemorrhage, antiplatelet therapy tends to be preferred over anticoagulation. 3,4 Still, analysis of data from a large singlecentre registry indicated that patients with intracranial artery dissection without subarachnoid hemorrhage had a favourable outcome with anticoagulants.…”
Section: Management Of Carotid Dissectionmentioning
confidence: 85%
“…There is currently no evidence for superiority of either therapy. 4 The Cervical Artery Dissection in Stroke e4 Stroke…”
Section: Discussionmentioning
confidence: 99%
“…9 However, this practice is not confirmed by nonrandomized studies and randomized trials are missing. 10 Moreover, anticoagulation has to be used carefully in case of extensive ischemic stroke due to hemorrhagic transformation risk, and subarachnoid hemorrhage, a potential complication of intracranial VAD, has to be looked for before any antithrombotic therapy can be proposed. 9 …”
Section: Discussionmentioning
confidence: 99%